Pemetaan Budaya Suku Dayak Tomun di Sekitar Kota/Kabupaten Lamadau Provinsi Kalimantan Tengah Untuk Penunjang Pariwisata Kota dan Pemberdayaan Masyarakat Lokal - Yophie Septiady; Uras Siahaan; Ramos Pasaribu; James Rilatupa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2022)
Lamandau Regency which is known to have a unique culture, because there is a relationship between the Dayak Tomun tribe which is more or less influenced by Minang culture from the Pagaruyung Kingdom in West Sumatra. In every community life is regulated or organized by customs, and rules regarding various kinds of units in the environment in which they live and socialize from day to day. Of course, this cultural mapping and community readiness is important, because it is related to local community acceptance and the development planning of Lamandau City itself. The materials used in this investigation are several locations of the Dayak Tomun tribe ecosystem around the City of Lamandau Regency. The ecosystem can be in the form of villages or villages of the Tomun Dayak tribe who still carry out and maintain the preservation of their tribal culture. To be able to do this, the investigation method was carried out by visiting each location of the cultural ecosystem of the Dayak Tomun tribe around the City of Lamandau Regency. Then determine the locations that are considered potential. From the implementation of this community service, cooperation was obtained with the Lamandau Regency Government to find out the City Spatial Plan (RUTRK) of Lamandau City Regency related to tourism programs in its area.